PENERAPAN PEMBELAJARAN KONTEKSTUAL UNTUKMENINGKATKAN KETERAMPILAN MENDESKRIPSIKAN SECARA TERTULIS PADA SISWA KELAS II.C SD NEGERI 82 KOTA BENGKULU SEMESTER II TAHUN PELAJARAN 2014/2015 - Suriatmi SUriatmi (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2016)
The aim of this study is how to improve the students skills to make descriptive written review using Contextual Teaching and Learning ( CTL ) instructional method, by utilizing animal pictures as a learning tool. Research design was a Classroom Action Research ( CAR). Research subject was Class II.C sttudents SDN 82 Kota Bengkulu (28 students). Research results indicates an increase of students ability to make descriptive writing. Improvement of learning achievement seen from the increased of the students ability after learning treatment. Before learning treatment, just 28.57% of students ( 8 of 28 students ); and after the first cycle increased to 50 % of students ( 14 of 28 students ) ; and after the third cycle increased by 85.71 % of students ( 24 of 28 students ) which passed the assessment indicators are set